Expansion by eigenvectors in case of simple eigenvalues of singular differential operator - Makhnei, O.V.; Tatsii, R.M. (Carpathian Mathematical Publications, 2011)
The asymptotic formulas with large values of parameter for solutions of singular differential equation allow us to estimate Green's function of the boundary-value problem. With the help of this estimation the expansion of singular differential operator by eigenvectors in the case of simple eigenvalues is constructed.